Pesticide residues in plums from field treatment to the drying process - Cabras, P.; Angioni, A.; Garau, V. L.; Minelli, E. V.; Cabitza, F.; Cubeddu, M. (Chiriotti Editori, 1998)
The fate of three pesticides (vinclozolin, dimethoate, cyproconazole) in plums, from field treatment to the drying process, was studied. Only vinclozolin showed measurable residue concentrations at harvest, while dimethoate was completely degraded after two weeks and cyproconazole was present at negligible levels just after treatment. During the drying process into prunes, the residues were not reduced during the fruit washing stage, but the drying stage led to complete elimination of vinclozolin residues.
Keywords: cyproconazole; dimethoate; pesticide; plums; prunes; residues; vinclozolin